2023
DOI: 10.3390/cimb45110540
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA and Inflammation in Alzheimer’s Disease

Giacoma Galizzi,
Marta Di Carlo

Abstract: Mitochondrial dysfunction and neuroinflammation are implicated in the pathogenesis of most neurodegenerative diseases, such as Alzheimer’s disease (AD). In fact, although a growing number of studies show crosstalk between these two processes, there remain numerous gaps in our knowledge of the mechanisms involved, which requires further clarification. On the one hand, mitochondrial dysfunction may lead to the release of mitochondrial damage-associated molecular patterns (mtDAMPs) which are recognized by microgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 189 publications
(235 reference statements)
0
7
0
Order By: Relevance
“…There is growing evidence indicating a connection between mitochondrial dysfunction and inflammatory responses in AD. 35 These dysfunctional mitochondria trigger a series of events that result in inflammation within the brain. Inflammatory responses, characterized by the release of proinflammatory mediators, exacerbate neuronal damage and contribute to the progression of AD pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence indicating a connection between mitochondrial dysfunction and inflammatory responses in AD. 35 These dysfunctional mitochondria trigger a series of events that result in inflammation within the brain. Inflammatory responses, characterized by the release of proinflammatory mediators, exacerbate neuronal damage and contribute to the progression of AD pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…In PD, it has been suggested that mitochondrial dysfunction can lead to the release of mitochondrial damage-associated molecular patterns (mtDAMPs), triggering neuroinflammation through microglial immune receptors. Conversely, inflammatory molecules released by the glial cells can further damage mitochondrial function, triggering a vicious circle that can lead to neurodegeneration [ 118 , 119 ]. In mental disorders such as major depression and schizophrenia, higher levels of cf-mtDNA were associated with symptoms of depression and schizophrenia.…”
Section: Mitochondria and Cns Diseasesmentioning
confidence: 99%
“…Currently, Aβ42and phosphorylated tau proteins are the main fluid-based biomarkers of Cerebrospinal fluid (CSF) in clinical practice ( Bălaşa et al, 2020 ). However, there are still limitations in their specific detection based on their low concentration in blood ( Noble et al, 2014 ; Galizzi and Di Carlo, 2023 ). As mentioned, inflammation plays a major role in AD development and among all different neuroinflammatory biomarkers which can be considered as therapeutic targets for drug design, cytokines, chemokines and transcription factors for their precise roles in the various stages of AD, possible medical applications, and easy isolation from blood or CSF have attracted a lot of attention ( Zheng et al, 2016 ; AmeliMojarad et al, 2022 ; Park et al, 2022 ).…”
Section: Inflammatory Biomarkers and Admentioning
confidence: 99%